2013
DOI: 10.1007/s00394-012-0485-3
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with tocotrienol-rich fraction alters the plasma levels of Apolipoprotein A-I precursor, Apolipoprotein E precursor, and C-reactive protein precursor from young and old individuals

Abstract: TRF appears to not only affect plasma levels of tocopherols and tocotrienols, but also the levels of plasma proteins. The identity of these proteins may provide insights into how TRF exerts its beneficial effects. They may also be potentially developed into biomarkers for the study of the effects and effectiveness of TRF supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 46 publications
3
23
1
1
Order By: Relevance
“…Results from the present study indicated that short-term TRF administration was unable to improve CRP levels in HD patients. This is in contrast with a recent TRF trial that has been conducted in healthy volunteers which showed reduction in CRP levels in older subjects 22. We speculate that this is partially due to high inter-individual variability in CRP levels, which is often associated with transient intercurrent clinical events and the dynamic response of immune system 45.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Results from the present study indicated that short-term TRF administration was unable to improve CRP levels in HD patients. This is in contrast with a recent TRF trial that has been conducted in healthy volunteers which showed reduction in CRP levels in older subjects 22. We speculate that this is partially due to high inter-individual variability in CRP levels, which is often associated with transient intercurrent clinical events and the dynamic response of immune system 45.…”
Section: Discussioncontrasting
confidence: 61%
“…However, in vivo, antioxidative properties of TT could be limited by physiological processes (eg, absorption, distribution, metabolism, and excretion), but TT have been found to be as equally potent as TP 19,20. More importantly, TT also play a role beyond their known antioxidant activity – ie, they possess an anti-inflammatory property which has been shown to inhibit lipopolysaccharide-induced secretion of interleukin (IL)-6 and tumor necrosis factor in macrophages,21 and decreased C-reactive protein (CRP) in human volunteers 22. Additionally, TT may also confer cardioprotective effects by improving lipid profiles (reduced total cholesterol and TAGs),23,24 and lower oxidation of LDL cholesterol 25…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A topical formulation containing tocopherols and tocotrienols showed photoprotective effect in photosensitive subjects [145]. Supplementation of tocotrienol-rich fraction (74% tocotrienol and 26% tocopherols) modulated plasma proteins including CRP in healthy female subjects [146]. Patel et al [147] reported that tocotrienol mixtures (200mg, n=14) exhibited stronger protective effect than αT (n=5) on end-stage liver disease in cirrhosis patients with hepatitis B and C. In addition, Tamoxifen combined with γTE showed non-significant decrease of breast cancer mortality compared with tamoxifen alone controls [148].…”
Section: Health Benefits In Human Clinical Studiesmentioning
confidence: 99%
“…Heng and colleagues reported the effect of TRF supplementation and modulation of protein expression in young and old individuals [37]. Each group was further separated into placebo and TRF arm and supplemented for six months.…”
Section: Other Clinical Effectsmentioning
confidence: 99%